A case study of developing ICT-supported pedagogy through a collegial practice transfer process. (1st December 2015) - Lakkala, Minna; Ilomäki, Liisa
Abstract: A collegial practice transfer process between more- and less-experienced teachers was examined in two cases that sought to encourage teachers to use information and communication technology (ICT) in a pedagogically meaningful way. Collegial practice transfer aims to offer new models for in-service teacher training. The process included guiding sessions, training materials presenting authentic pedagogical examples, and try-outs in the classroom. The success of practice transfer was examined through comparing the classroom practices of more- and less-experienced teachers applying the Pedagogical Infrastructure Framework, and through analyzing the tutored teachers' self-reported experiences in interviews. The process provided flexible support and gave self-confidence to the less-experienced teachers. Technology use was successful, but the tutored teachers designed less coherent tasks and weaker support for pupils' collaboration, knowledge construction and metacognition than their more-experienced colleagues. When tutoring, underlying educational ideologies and reasons should be explicated in addition to practical issues of classroom orchestration and technology use. Highlights: Collegial tutoring inside a school is a flexible ICT training method for teachers. Tutoring encourage novice teachers to try new practices with ICT in teaching. Support for cultivating pedagogical approaches is more critical than technology use.